2020
DOI: 10.3390/genes11040415
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Corpus luteum Reveals Important Insights about Early Pregnancy in Domestic Sheep

Abstract: The majority of pregnancy loss in ruminants occurs during the preimplantation stage, which is thus the most critical period determining reproductive success. Here, we performed a comparative transcriptome study by sequencing total mRNA from corpus luteum (CL) collected during the preimplantation stage of pregnancy in Finnsheep, Texel and F1 crosses. A total of 21,287 genes were expressed in our data. Highly expressed autosomal genes in the CL were associated with biological processes such as progesterone forma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 92 publications
(112 reference statements)
2
21
0
Order By: Relevance
“…Several studies have reported that MGP is highly expressed in the bovine endometrium (Spencer et al 1999, Mamo et al 2012. The high level of MGP expression in our current and previous (Pokharel et al 2020) studies is consistent with earlier reports where this gene was found to be elevated during the preimplantation stage in sheep (Spencer et al 1999, Gray et al 2006) and cattle (Mamo et al 2012). Similarly, Casey et al (2005) reported that MGP was significantly upregulated in nonregressed compared to regressed bovine CLs.…”
Section: Most Highly Expressed Genessupporting
confidence: 92%
See 3 more Smart Citations
“…Several studies have reported that MGP is highly expressed in the bovine endometrium (Spencer et al 1999, Mamo et al 2012. The high level of MGP expression in our current and previous (Pokharel et al 2020) studies is consistent with earlier reports where this gene was found to be elevated during the preimplantation stage in sheep (Spencer et al 1999, Gray et al 2006) and cattle (Mamo et al 2012). Similarly, Casey et al (2005) reported that MGP was significantly upregulated in nonregressed compared to regressed bovine CLs.…”
Section: Most Highly Expressed Genessupporting
confidence: 92%
“…be induced by the progesterone and are critical for conceptus elongation (Brooks et al 2014). We observed high abundance of key genes involved in progesterone production in the CL of the studied animals (Pokharel et al 2020) which complements findings from this data. This is consistent with maximal production of IFNT which causes massive changes in the endometrial gene expression starting Day 13 of pregnancy (Gray et al 2006, Forde and Lonergan 2017.…”
Section: Differentially Expressed Genes In the Endometrium Having Sphsupporting
confidence: 87%
See 2 more Smart Citations
“…After 2–3 weeks of pregnancy, the ewes were slaughtered to collect the tissue biopsies of corpus luteum (CL) and endometrium for inclusion in this study. Procedures for RNA extraction, sample quality control measurements and sequence library preparation have been described previously (Hu et al, 2015; Pokharel et al, 2020). High‐quality libraries of miRNA were sequenced with an Illumina HiSeq 2000 system using single‐end (1 × 50) sequencing strategy.…”
Section: Figurementioning
confidence: 99%